2021
DOI: 10.1542/hpeds.2020-005074
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pediatric Emergency Department Visits During the COVID-19 Pandemic

Abstract: OBJECTIVES: Community mitigation measures were implemented to decrease the spread of severe acute respiratory syndrome coronavirus 2. In this study, we aimed to evaluate changes in pediatric emergency department (ED) visits, secondary to acute respiratory illnesses (ARIs) and trauma, before and during the pandemic. We hypothesized that the numbers of ED visits and ARIs would decrease, whereas the proportion of trauma visits would increase. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 8 publications
4
34
0
6
Order By: Relevance
“…Data from one US medical centre reported a significant drop in pediatric ED visits for acute respiratory illnesses over 3 months (March–May 2020) compared to previous years. [ 17 ] This pattern is supported here with national data across a whole year from Israel, and excluding patients ultimately found to be COVID-19 positive, allowing a comprehensive analysis of changing ED use in relation to the timing of the pandemic peaks of increased infection incidence.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Data from one US medical centre reported a significant drop in pediatric ED visits for acute respiratory illnesses over 3 months (March–May 2020) compared to previous years. [ 17 ] This pattern is supported here with national data across a whole year from Israel, and excluding patients ultimately found to be COVID-19 positive, allowing a comprehensive analysis of changing ED use in relation to the timing of the pandemic peaks of increased infection incidence.…”
Section: Discussionsupporting
confidence: 59%
“…Studies of asthma in the United States during the COVID-19 pandemic have shown reduced hospitalizations, fewer ED visits, and improved asthma control during the pandemic, and have linked these favourable outcomes to lockdowns and school closures [ [17] , [18] , [19] , [20] , [21] ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall drop in ED visits during the pandemic seen in this study has been documented by other investigators. 9 , 10 Yet when examining specific complaints, an increase in the percentage of community masking was reflected in a drop in ED visits for non-COVID viral illness and exacerbations of asthma exacerbations and COPD in this retrospective multi-site study. These findings suggest the well-known decrease in person-to-person transmission of respiratory viruses due to masking 4 also has a measurable and positive impact on health systems.…”
Section: Discussionmentioning
confidence: 78%
“…These restrictions, in conjunction with local “stay at home” orders, resulted in a significant decline in hospital-based healthcare services across the globe, including imaging and emergency services [ 4 6 ]. ED patient visit volumes decreased 40–75% [ 7 – 9 ], and ED imaging volumes decreased by 28–58% [ 10 – 14 ]. While some proportion of the decreased healthcare utilization is thought to be deferral of elective care [ 15 ], a number of studies have also found visits for emergent conditions, such as ST-elevation myocardial infarction and stroke also decreased in the early pandemic [ 16 20 ].…”
Section: Introductionmentioning
confidence: 99%